THE EFFECTIVENESS OF FREQUENCY IN GIVING ASSIGNMENTS ON ENGLISH LEARNING OUTCOMES AT GRADE SIXTH STUDENTS OF GLOBAL PERSADA MANDIRI ELEMENTARY SCHOOL - NOVITA AISYAH REZKI LUBIS; YON A.E (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2023)
Purpose of The Research is to find out the effectiveness of frequency in giving assignments on English learning outcomes at grade 6th students at Global Persada Mandiri Elementary School Bekasi. The instrument for obtaining research data was the results of test given to students in two different classes with different methods of giving. The method of this research is experiment method, the population was all class VI students at SD Global Persada Mandiri Bekasi. This research involving 60 samples which taken randomly. Based on the result of the research conducted, it is proven that there is an effect of the frequency of assignments on English learning outcomes with the results of the control class research calculations where the mean value is (65,9), median (64,6), and the mode(65,1) for the experimental class obtained a mean value of (73,9), median (71,2) and mode (72,5). Then the results of the hypothesis test a fairing of 3,88 and of 1,644. In testing the H0 it is rejected if is greater than . The results of the t-test show that > where 3,88>1,644. So it can be concluded that there is an effect of the frequency in giving assignments on the English learning outcomes at grade sixth of Global Persada Mandiri Bekasi. ABSTRAKTujuan Penelitian adalah untuk mengetahui efektivitas frekuensi pemberian tugas terhadap hasil belajar bahasa Inggris pada siswa kelas 6 SD Global Persada Mandiri Bekasi. Instrumen untuk memperoleh data penelitian adalah hasil tes yang diberikan kepada siswa di dua kelas yang berbeda dengan metode pemberian yang berbeda. Metode penelitian ini adalah metode eksperimen, populasinya adalah seluruh siswa kelas VI SD Global Persada Mandiri Bekasi. Penelitian ini melibatkan 60 sampel yang diambil secara acak. Berdasarkan hasil penelitian yang dilakukan terbukti terdapat pengaruh frekuensi penugasan terhadap hasil belajar bahasa Inggris dengan hasil perhitungan penelitian kelas kontrol dimana nilai mean (65,9), median (64, 6), dan modus (65,1) pada kelas eksperimen memperoleh nilai mean (73,9), median (71,2) dan modus (72,5). Kemudian hasil uji hipotesis fairing sebesar 3,88 dan sebesar 1,644. Dalam pengujian H0 ditolak jika lebih besar dari . Hasil uji t menunjukkan > dimana 3,88>1,644. Jadi dapat disimpulkan bahwa terdapat pengaruh frekuensi pemberian tugas terhadap hasil belajar bahasa Inggris kelas VI Global Persada Mandiri Bekasi.